Analisis Pengendalian Kualitas Produk Kapasitor di PT XYZ Batam - Defvi Marriauwaty; Fajrah, Nofriani (AGUSPATI Research Institute, 2020)
Competition in the industry, both services and manufacturing, is not only on the scale of the company or its human resources, but also on the quality of products produced. The company needs to take quality control measures to maintain the quality of their products to comform to the quality standards set by the company, so that their products can be accepted by consumers. PT XYZ Batam is a capacitor manufacturing company. In the production process there are still various and fluctuating defects. The purpose of this study was to identify the level of variation in defects in the production process, identify the level of quality control performance by finding the value of DPMO, and identify the causes of defects. Map p is used to determine the number of defective products, DPMO is used to determine the level of sigma level and fishbone diagrams are used to identify the causes of defects. The results showed that there were data out of control limits on less / low epoxy and epoxy on lead defects while in off center and epoxy on box defects there was no data out of control. This value is still relatively low. Based on the fishbone diagram, it was found that human, machine, method, material and environmental factors were the cause of defects in capacitor production.